A revised annotated checklist of louse flies (Diptera, Hippoboscidae) from Slovakia - Oboňa, Jozef; Sychra, Oldřich; Greš, Stanislav; Heřman, Petr; Manko, Peter; Roháček, Jindřich; Šestáková, Anna; Šlapák, Jan; Hromada, Martin (ZooKeys, 2019)
The list of all known locality and host records from the literature on louse flies from Slovakia are summarized, with the addition of new collection data. New locality data are provided for five species. Three species are added to the Slovakian list: Icostaminor (Bigot in Thomson, 1858), which was erroneously cited for Moravia instead of Slovakia in the previous checklist, and Ornithophilametallica (Schiner, 1864) and Ornithomyachloropus (Bergroth, 1901), which were overlooked from the last checklist. As a result, the louse fly fauna of Slovakia increases to 19 species: 12 autochtonous species and seven rare, non-native species only occasionally imported to Slovakia or migrating to the country with their hosts. This is by far the largest regional fauna of Hippoboscidae in Central Europe, and matches the richest southern European faunas. In total, 78 host-parasite associations concerning 46 bird-host species from eight orders and nine species of mammals, including humans, have been found from a literature review in Slovakia. Two host-parasite associations are reported from Slovakia for the first time: Ornithomyaavicularia (Linnaeus, 1758) on Prunellamodularis (Linnaeus, 1758) (Aves: Prunellidae) and Lipoptenafortisetosa Maa, 1965 on Homosapiens Linnaeus, 1758 (Mammalia: Hominidae).
Keywords: Faunistics; louse flies; parasite-host associations; literature review